The three musketeers (New York : Waldman & Son, 1977)
"One for all and all for one!" was the rousing cry of the bold Musketeers and the young cadet, D'Artagnan. Follow their exciting adventure as they save the honor of the Queen and outwit the powerful Cardinal Richelieu and his murderous spies.
Keywords: Adventure and adventures